2004
DOI: 10.1002/jbm.b.30007
|View full text |Cite
|
Sign up to set email alerts
|

Poly(vinyl alcohol) membranes for adhesion prevention

Abstract: The abnormal joining of anatomic structures after abdominal and pelvic surgery can lead to such major complications as bowel obstruction or infertility. Poly(vinyl alcohol) (PVA) membranes and hydrogels were placed over the injured tissue to act as a physical barrier and prevent such adhesions from occurring in a rabbit sidewall model. The membranes were sutured into place to prevent their slipping or curling on the moist tissue. Various in vitro experiments (including testing for swelling and mechanical stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(77 citation statements)
references
References 60 publications
3
73
0
1
Order By: Relevance
“…As an antiadhesive material, findings have shown Seprafilm to be highly effective in reducing both the incidence and severity of adhesion formation to midline abdominal closures in humans [18]. Although Seprafilm is highly effective in preventing adhesions to the PPM [19,23], its adhesional barrier provides definite but incomplete inhibition of visceral adhesions to the PPM [20,21].…”
Section: Discussionmentioning
confidence: 98%
“…As an antiadhesive material, findings have shown Seprafilm to be highly effective in reducing both the incidence and severity of adhesion formation to midline abdominal closures in humans [18]. Although Seprafilm is highly effective in preventing adhesions to the PPM [19,23], its adhesional barrier provides definite but incomplete inhibition of visceral adhesions to the PPM [20,21].…”
Section: Discussionmentioning
confidence: 98%
“…25 No adhesions could be detected in 75% of the rabbits treated with A-part 1 . In our setup Adept 1 showed no effect as an antiadhesive prophylaxis agent.…”
Section: In Vivo Adhesion Prevention By A-partmentioning
confidence: 94%
“…A-Part ® gel is a bioabsorbable transparent gel composed of PVA and CMC [ 25 ] . Material characteristics such as viscosity and adherence to the wound were tested with good results [ 26,27 ] . Preclinical data in animal studies revealed high effi cacy in adhesion prevention, and wound and anastomosis healing were not negatively affected by the application of this gel in animal models.…”
Section: Gelsmentioning
confidence: 99%